Early Human Occupation in the Southern Part of the Deseado Massif (Patagonia, Argentina) - Franco, Nora Viviana (2010)
Human occupation sites dating to the Pleistocene-Holocene transition have been identified in the Deseado Massif, Patagonia (e.g., Cardich et al. 1973; Miotti et al. 1999; Miotti and Salemme 2003, 2004; Paunero 2000a, 2000b, 2009; Paunero et al. 2007). However, south of the Massif, the earliest evidence of human occupation dates to the early Holocene, ca. 8900 RCYBP at El Verano (Durán et al. 2003) and ca. 8050 RCYBP at La Martita Cave 4 (Aguerre 2003). There has been no previous systematic archaeological research in the Deseado Massif south of El Verano and La Martita Cave 4 sites. However, this area is crucial to our understanding of the initial peopling of southern Patagonia because, although the Massif contains numerous caves as well as excellent rocks for flintknapping (sensu Aragón and Franco 1997; Callahan 1979), similar resources are scarce to the south (e.g., Echeveste 2005; Franco and Cirigliano 2009; Franco et al. 2009; Panza and Franchi 2002; Panza and Haller 2002; Panza and Marin 1998; Russo and Flores 1972; Russo et al. 1980). Research in nearby areas indicates that variations in these resources from one area to another, as well as differences in the availability of water, had a significant impact on early human populations (e.g., Borrero and Franco 2000; Goñi et al. 2000–2002; Franco et al. 2007).